2008
DOI: 10.1068/c0643
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Sourcing by Foreign-Owned Subsidiaries

Abstract: This paper investigates the development of domestic sourcing by foreign-owned subsidiaries (FOS) in the UK. The regional development and international-business literatures are used to develop a conceptual framework on the links between autonomy, the use of networks, and domestic sourcing. Data from a survey of German, French, and US FOS in the UK is used to test the model. The results indicate that increased use of networks and increased operational decision-making autonomy are associated with increased domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…Second, the duration from establishment to 2006 was used to measure the age of firm (AGE). In general, there is a trend of increasing local embeddedness over time, including increasingly using local personnel for top management positions (Iguchi, 2008;Williams, 2005;Williams et al, 2008). Third, firms with more R&D capacities in China tend to have more resources and incentives to develop local technological linkages (Sun & Du, 2011).…”
Section: Research Setting Data and Methodologymentioning
confidence: 97%
See 3 more Smart Citations
“…Second, the duration from establishment to 2006 was used to measure the age of firm (AGE). In general, there is a trend of increasing local embeddedness over time, including increasingly using local personnel for top management positions (Iguchi, 2008;Williams, 2005;Williams et al, 2008). Third, firms with more R&D capacities in China tend to have more resources and incentives to develop local technological linkages (Sun & Du, 2011).…”
Section: Research Setting Data and Methodologymentioning
confidence: 97%
“…We focus on TNCs' backward and technological linkages with local firms, which are central issues in the literature on embeddedness and are key components in the process of coupling with TNCs in the GPN (Dunning, 1993;Sun & Du, 2011;Williams et al, 2008). We hypothesize that the backward and technological linkages between TNCs and local firms are not automatic.…”
Section: Theoretical Issues and Research Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…Autonomy is also needed for subsidiaries to take on export roles, and it has been found that autonomous subsidiaries have high propensity to export . As for any initiative, subsidiaries require resource support and are largely dependent on parent firm resourcesliterature suggests that subsidiaries in New Zealand largely draw on parent firm resources (Scott-Kennel, 2001), and though subsidiaries could get funding from external and domestic sources as well, majority get resources from parent firms (Dutton et al, 1999;Williams et al, 2008).…”
Section: Conceptual Frameworkmentioning
confidence: 98%